2019
DOI: 10.1108/nfs-04-2019-0132
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in taste and foods habits

Abstract: Purpose -The purpose of this paper is to examine gender differences in food habits and food choices, including decisions in healthy eating, to personalize diet therapies to be as effective possible for long-term weight loss.Design/methodology/approach -In this cross-sectional study, eating behaviours were assessed using a questionnaire composed of 12 questions concerning food habits, 17 concerning food taste, and four about healthy eating. There were 2,021 (1,276 women) Caucasian adults enrolled in the study.F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 29 publications
4
48
1
Order By: Relevance
“…Women also reported a lower familiarity than men with fatty meat and cold meat. These results were in line with previous studies that reported a lower intake of meat in women [15,73]. In addition, this study showed that this was true independent of fat content.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Women also reported a lower familiarity than men with fatty meat and cold meat. These results were in line with previous studies that reported a lower intake of meat in women [15,73]. In addition, this study showed that this was true independent of fat content.…”
Section: Discussionsupporting
confidence: 93%
“…Gender has the largest impact on sensory response and food preferences [13] and was found to affect liking and consumption of meat and fat products, with women liking meat [14][15][16] and high-fat products [17] less than men. Furthermore, women reported more avoidance of fats from meat than men did [10,18,19], and a study across 22 countries showed that gender had the most consistent influence on fat preference in pork meat among other factors, with a greater proportion of women than men preferring pork with less fat cover [20].…”
Section: Introductionmentioning
confidence: 99%
“…This finding may also point to the complexity of a sex relationship with suicidal ideation/attempt, as there are also suggestions of an underlying mechanism to sex difference in food choice and preferences including sweet tastes [ 58 ]. The possible role of culture in framing the relationship of sex and suicidal ideation/attempt [ 60 ] and moderating sex differences in taste preferences [ 61 , 62 ] needs to be explored further to explain the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…As a previous study demonstrated gender-specific differences concerning eating habits, food taste and relationship with food, the authors also suggested the development of gender-specific programs for the promotion of a healthy lifestyle. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%